Kajian potensi jalan alternatif Gedongtataan-Beranti ditinjau dari penghematan waktu dan biaya - Arief Budi Atmoko (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
Along with the development of the region, the road to Radin Intan II Airport is now very crowdedand jammed so that it takes an alternative road. This study examines the potential for an alterna-tive way to Gedongtataan – Branti terms of saving time and cost. Car survey method used to de-termine the value of time travel saving taken while the observational method used to determinethe Vehicle Operating Costs (VOC). From the results of the discussion and analysis has been doneto obtain the benefits of development of the travel time and cost savings is the magnitude of thevalue of time savings for 5 years Rp 69.377.544.884,00 and then compared with the estimated costof construction Rp. 66.500.000.000,00, So the value of the benefits of road construction is aboutRp 2.877.544.884,00 and the value of vehicle operating costs for 5 years Rp. 67.161.235.626,00compared with the estimated cost of construction Rp. 66.500.000.000,00 so value of benefits aboutRp. 661.235.626,00. While this is still a global picture of the way benefits are worth the time andvehicle operating costs. If further study on the benefits that are not measurable (intangible bene-fits) such as regional development, community economic enhancement, smooth movement, pollu-tion reduction and so on, then the benefits will be far greater.